2010
DOI: 10.1071/rj09069
|View full text |Cite
|
Sign up to set email alerts
|

Forb responses to grazing and rest management in a critically endangered Australian native grassland ecosystem

Abstract: Worldwide, temperate grasslands have been extensively cleared for agriculture and urban expansion and the ‘Natural Temperate Grassland of the Victorian Volcanic Plain’ in south-eastern Australia has recently been listed as critically endangered. Because of land clearing, these grasslands now occupy <1% of their original distribution and much of the remaining grassland continues to be grazed by livestock. Although forbs (wildflowers) constitute most of the floristic richness in natural grasslands, few experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…spring) has been shown to maintain native forb richness and grass cover (Leonard & Kirkpatrick ; Zimmer et al . ; Mavromihalis et al . ; Fedrigo et al .…”
Section: Discussionmentioning
confidence: 99%
“…spring) has been shown to maintain native forb richness and grass cover (Leonard & Kirkpatrick ; Zimmer et al . ; Mavromihalis et al . ; Fedrigo et al .…”
Section: Discussionmentioning
confidence: 99%
“…2007; McIntyre & Lavorel 2007; Lewis et al. 2008; Zimmer et al. 2010), but the lack of application of fire as a disturbance may also be an important factor limiting change.…”
Section: Discussionmentioning
confidence: 99%
“…Grazing duration is also known to be as deleterious to pasture condition as grazing density (Scarnecchia & Kothmann 1986; Vallentine 2001). Therefore, we calculated a combined grazing intensity (GI) index and concluded that 11 TSRs were moderately (GI > 2; six sites) to heavily grazed (GI > 3, six sites).…”
Section: Discussionmentioning
confidence: 99%
“…Grazing in spring can deleteriously affect plant species when flowering and seed set take place (Bullock et al. 2001; Zimmer et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation